Pakistan Chronicle - U.A.B. Razia Akter Banu (American Journal of Islam and Society, 1997)
The book Pakistan Chronicle--authored by Morrice James, who had twenty years of experience in South Asia, of which nine years were in Pakistan as deputy and head of the United Kingdom's diplomatic mission-may not be an excellent academic research document, but it deserves credit for certain merits. The psychoanalyses and behavioral studies of some Pakistani military and political elite, especially Ayub, Bhutto, and Zia, are some of the book's outstanding contributions. The book contains excellent discussions on different pacts and treaties Pakistan conducted, such as the Mutual Assistance Pact with the United States (1954), the Indus Water Treaty (1960), the Tashkent Declaration (1966); the crises Pakistan faced, such as the anti-Qadiani Riots in 1953, the Kashmir dispute, and the Bangladesh War in 1971; and the Afghan conflict that involved the two superpowers. In the 1960s. the author observed that India considered Kashmir an integral part of itself and nonnegotiable, and that position has not yet changed. As the British high commissioner, the author could give a firsthand description of national and international forces that strained Pakistan’s relationship with the West, especially Britain and America, and of how Pakistan gradually developed a pro-Chinese foreign policy ...